EVALUASI KEBIJAKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 5 TAHUN 2002 - Roza, Aldi; Harahap, Tuti Khairani; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2019)
Policy Evaluation of Pekanbaru City Regulation Number 5 of 2002. This study aims to determine Regional Regulation Number 5 of 2002 concerning Public Order in the City of Pekanbaru. This study uses a qualitative approach, with descriptive methods. Sources of data were obtained from primary data sources, through direct observation and interviews with key informants, namely Pekanbaru City DPRD Members, Governmental Assistant I, Head of Pekanbaru City Satpol PP, Secretary of the Market Service, Chair of the Pekanbaru City Market Traders Association, Chairperson of the Morning Market Traders Association Arengka, PKL in the Kodim Market, PKL in Arengka Market and Community Representatives. Data analysis techniques used the tringulation method by comparing the results of interviews with the government and street vendors in the field. The results of the study show that the Pekanbaru City Regulation Regulation Number 5 of 2002 concerning Public Order Policy has not been fully understood and adhered to by street vendors.